Brontë's Jane Eyre - Brennan, Zoe, 1971- (Continuum reader's guides., 2010)
Charlotte Brontë's Jane Eyre is one of the most famous literary works of the nineteenth century and has inspired generations of students. This concise but comprehensive guide to the text introduces its contexts, language, reception and adaptation from its first publication to the present. It includes points for discussion, suggestions for further study and an annotated guide to relevant reading. This introduction to the text is the ideal companion to study, offering guidance on: Literary and historical context. Language, style and form. Reading the text. Critical reception and publ.